MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU DAN DAYA SAING SEKOLAH DI SD IT ROBBANI RANTAUPRAPAT SUMATERA UTARA - Nur Indri Yani Harahap; Supratman Zakir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research discusses the challenges at SD IT Robbani Rantauprapat, North Sumatra, regarding the quality of education despite having a structured curriculum. Limited facilities, textbooks, technology and educators are obstacles but also opportunities for innovation. With careful planning, educator development and effective training, the school distributes resources evenly, improves teachers' competencies and applies transparent performance appraisals and evaluations to create a conducive learning environment. This study aims to explain the planning, organizing, implementing, and monitoring of human resource management to improve the quality and competitiveness of the school in the 2023/2024 school year. The approach used is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The informants consisted of the principal as the key informant, as well as the vice principal for curriculum, the head of administration, and teachers as supporting informants. Data analysis included data reduction, presentation, and conclusion drawing, with validation through data triangulation. The results show that human resource management supports school quality and competitiveness through vision-mission-based strategic planning, efficient organization, inclusive implementation and systematic supervision. This approach strengthens school competitiveness in the era of competitive education.